New species and records of Microveliinae and Veliinae (Hemiptera: Heteroptera: Veliidae) from Colombia - Molano, Fredy; Moreira, Felipe Ferraz Figueiredo; Morales, Irina (Zootaxa, 2016)
Euvelia orinoquia sp. nov. and E. meta sp. nov. from eastern Colombia are described, illustrated, and included in an updated identification key to the species of the genus. The former can be diagnosed by body length 2.30–2.50 mm, male fore femur without tufts of setae, longitudinal black stripe of female pronotum almost twice as wide as length of antennomere I, and female connexiva grayish black with silvery pruinosity on mesal portion, reddish on lateral portion. Euvelia meta sp. nov. can be diagnosed by female body length about 1.50 mm and maximum body width 0.90 mm, patches of silvery setae on female abdominal terga II–III and V–VII, and connexival segments I and IV–VI. Additionally, new records from the country are presented for species of Euvelia Drake, Husseyella Herring, Microvelia Westwood (Microveliinae), Oiovelia Drake & Maldonado-Capriles, Platyvelia Polhemus & Polhemus, Stridulivelia Hungerford, and Veloidea Gould (Veliinae).